2019
DOI: 10.9734/jabb/2019/v21i130080
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Study of Antagonistic Capability of Trichoderma harzianum against Aspergillus niger Isolated from Rotten White Yam (Dioscorea rotundata) Tubers

Abstract: In vitro antagonistic study using dual culture technique was carried out at Advanced Plant Pathology Laboratory, Federal University of Agriculture, Makurdi, Nigeria to assess the potential capability of Trichoderma harzianum as a biocontrol agent against Aspergillus niger isolated from rotten yam tubers. The test antagonist (T. harzianum) was introduced at three different times (same time with pathogen, two days before the inoculation of the pathogen and two days after the inoculation of the pathogen). The pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…The findings showed that the three most common fungal pathogenic organisms in both yam tuber cultivars are A. niger, Penicillium, and Fusarium. This outcome is consistent with those of [22] and [23] who discovered that these pathogenic organisms were the worst rot-causing organisms in yam tubers in various parts of Nigeria.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings showed that the three most common fungal pathogenic organisms in both yam tuber cultivars are A. niger, Penicillium, and Fusarium. This outcome is consistent with those of [22] and [23] who discovered that these pathogenic organisms were the worst rot-causing organisms in yam tubers in various parts of Nigeria.…”
Section: Discussionsupporting
confidence: 92%
“…Thirty samples of yam, fifteen (15) of which were healthy and fifteen (15) of which were unhealthy, were gathered from five different farms in the Osisioma Ngwa Local Government Area of Abia State, Nigeria. The samples were sent to the lab for quick microbiological investigation in sterile plastic containers.…”
Section: A Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The result conforms to the report of Gwa and Ekefan (2017) indicating that the antagonist has the potential for biological control of Colletotrichum spp., and when T. harzianum tested against Fusarium spp., a significant disease reduction, was obtained in cotton, melon and tomato (Panwar et al, 2014;Sivan & Chet, 1986). As a biological control agent, it is potent and can be used to combat a variety of agricultural diseases of various crops.…”
Section: Bio-efficacy Trial On Selected Bca Under Field Conditionsupporting
confidence: 91%
“…(Table III). Trichoderma sp inhibitory effect using Sangoyomi scale (Gwa et al, 2019) was effective for five (5) of the isolated…”
Section: Resultsmentioning
confidence: 99%